FOREIGN CAPITAL FLOWS AND ECONOMIC GROWTH OF KENYA. - Ong'ondo, Wiberforce (International Journal of Finance and Accounting, 2018)
The purpose of the study was to establish the effects of foreign capital flows on economic growth of Kenya. The study employed a quantitative research design. The target population of this study was Kenya since it is the Center of analysis. Considering that the population is one country, Kenya, secondary data was collected over a period of 25 years from 1993 to 2017. Therefore, the number of observations was X * 25 = 25. The research conducted a census on Kenya using secondary data from Nairobi Securities Exchange (NSE), Capital Markets Authority (CMA), Kenya National Bureau of Statistics (KNBS), Central Bank of Kenya, World Bank and United Nations Conference on Trade and Development (UNCTAD). Data over time was analyzed using a time series model and trend analysis. Model test and correlation analysis were done before conducting regression and univariate regression analysis. The study found that, when external commercial borrowing is increased by one US dollar, annual GDP will increase by 395.990% when all other factors are kept constant. The opposite also applies. But, if external commercial borrowing is zero, annual GDP will decrease by USD 8,151,662,920.94 when all other factors are kept constant. Additionally, when Foreign Portfolio investment is increased by one US dollar, annual GDP will increase by 805.37% when all other factors are kept constant. The opposite also applies. But, if Foreign Portfolio Investment is zero, annual GDP will remain to be USD 25394237979 when all other factors are kept constant. Also, when FDI is increased by one US dollar, annual GDP will increase by 3026.30% when all other factors are kept constant. The opposite also applies. But, if FDI is zero, annual GDP will still increase by USD 18493289187.3 when all other factors are kept constant. Further results revealed that when Non-Resident Kenyan Deposits are increased by one US dollar, annual GDP will increase by 3738.65% when all other factors are kept constant. The opposite also applies. But, if Non-Resident Kenyan Deposits is zero, annual GDP will remain to be USD 4869680695.47 when all other factors are kept constant. The study recommends that the Government pursues policies that will attract and favour net increases in Foreign Direct Investments, Foreign Portfolio Investments, External Commercial Borrowings and Non-Resident Kenyan deposits into the country.